PERBEDAAN JUMLAH TROMBOSIT KONSENTRAT TROMBOSIT PADA PENYIMPANAN HARI I, III, V DI UNIT DONOR DARAH PMI PROVINSI BALI/RSUP SANGLAH DENPASAR - Lestariyani, Ni Kadek; Herawati, Sianny (E-Jurnal Medika Udayana, 2017)
Storage of platelet concentrate undergo some changes one of which is the count of platelet. The aim of study is to examine differences in the count of platelets concentrate on the day storage I, III, V. The study design was observational analytic which platelet concentrates obtain from volunteer donors who come to the unit donor darah PMI Provinsi Bali/RSUP Sanglah Denpasar. Platelet concentrate used as samples with the result HIV testing, Hapatitis B, Hepatitis C and VDRL are negative, without hemolysis and were prepared in June-August 2014. From 18 samples were used on the day I the mean value is 401.56±166.435, on the day III the mean value is 387.11±137.066 and on the day V the mean value is 338.00±106.536. Results of normality test p-value > 0,05. Which indicated hat Ho is accepted and normally distributed data. Results homegenitas test p-value 0,420 (p>0,05) indicating that Ho is accepted and data is homogeneous. ANOVA test showed p-value of 0, 362 so that significant difference in the average count of platelets in storage I, III, V. From this study it can be concluded that there is difference in platelet count is not significant. Some of the factors that caused are the presence of dextrose in anticoagulant were added to platelet concentrates, fragmentation on the platelet conncrates and good agitation during storage. Need for further research on the differences in the count of platelet concentrates with more sample.
Keywords: blood donation, platelet count, platelet concentrates